2016
DOI: 10.1164/rccm.201511-2178oc
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lung Function and Sleep-disordered Breathing on All-Cause Mortality. A Community-based Study

Abstract: Rationale: Whether sleep-disordered breathing (SDB) severity and diminished lung function act synergistically to heighten the risk of adverse health outcomes remains a topic of significant debate.Objectives: The current study sought to determine whether the association between lower lung function and mortality would be stronger in those with increasing severity of SDB in a communitybased cohort of middle-aged and older adults.Methods: Full montage home sleep testing and spirometry data were analyzed on 6,173 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Previous studies have suggested an inverse relationship between upper airway patency and the degree of hyperinflation . In a sample of 51 sleep apnoea patients derived from 10 192 smokers with and without emphysema from the COPDGene project who underwent high‐resolution chest‐computed tomography (CT) imaging and spirometry, Krachman and colleagues reported that CT‐derived per cent gas trapping was an important determinant for AHI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested an inverse relationship between upper airway patency and the degree of hyperinflation . In a sample of 51 sleep apnoea patients derived from 10 192 smokers with and without emphysema from the COPDGene project who underwent high‐resolution chest‐computed tomography (CT) imaging and spirometry, Krachman and colleagues reported that CT‐derived per cent gas trapping was an important determinant for AHI.…”
Section: Discussionmentioning
confidence: 99%
“…However, Putcha et al . demonstrated that the incremental contribution of lung function to mortality is attenuated with increasing SDB severity . The aim of this study was to investigate the influence of impaired lung function on incident stroke in a population of individuals with and without SDB from the Sleep Heart Health Study (SHHS), a large community‐based perspective cohort.…”
Section: Introductionmentioning
confidence: 99%
“…synergistic effect promotes the activation of the sympathetic nervous system, oxidative stress and systemic inflammation, which collectively contribute to vascular injuries and cardio-cerebral vascular incidents [3]. However, Putcha et al demonstrated that the incremental contribution of lung function to mortality is attenuated with increasing SDB severity [10]. The aim of this study was to investigate the influence of impaired lung function on incident stroke in a population of individuals with and without SDB from the Sleep Heart Health Study (SHHS), a large community-based perspective cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep apnoea is an independent risk factor for premature death (Putcha et al, 2016), with a wealth of evidence pointing to OSAS-related cardio-metabolic and neurocognitive dysfunction (McNicholas et al, 2007;Younes & White, 2012).…”
Section: Obstructive Sleep Apnoea Syndrome: Neurogenic and Myogenic Mmentioning
confidence: 99%